2002
DOI: 10.1002/bit.10451
|View full text |Cite
|
Sign up to set email alerts
|

Increase of the yields of eicosapentaenoic and docosahexaenoic acids by the microalga Pavlova lutheri following random mutagenesis

Abstract: The high commercial values of eicosapentaenoic (EPA) and docosahexaenoic (DHA) acids have driven a strain-improvement program, aimed at increasing the content of those fatty acids in the microalga Pavlova lutheri (SMBA 60) as parent strain. After a round of mutation using UV-light as mutagenic agent, an isolate strain (tentatively called II#2) was obtained, the EPA and DHA contents of which (in % dry biomass) were 32.8% and 32.9% higher than those of the control, native strain. The final EPA yields, when the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
33
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(36 citation statements)
references
References 22 publications
2
33
1
Order By: Relevance
“…The influence of light intensity on the lipid profile of Pavlova lutheri showed that cultures grown under low light intensity (9 Wm -2 ) had a higher fraction of EPA and DHA esterified in polar classes which had a favorable role in aquaculture (Catarina Guedes et al 2010). Application of the genetic engineering concept, by using u.v.-light as mutagenic agent generated strains with EPA and DHA contents about 32.8 and 32.9% (in % dry biomass) higher than those of the control, native strain (Meireles et al 2003). Use of process engineering, an on-line based controlled process in a model system has been employed to increase the production rates of both EPA and DHA by P. lutheri under various conditions of light and growth rate (Meireles et al 2008).…”
Section: Introductionmentioning
confidence: 94%
“…The influence of light intensity on the lipid profile of Pavlova lutheri showed that cultures grown under low light intensity (9 Wm -2 ) had a higher fraction of EPA and DHA esterified in polar classes which had a favorable role in aquaculture (Catarina Guedes et al 2010). Application of the genetic engineering concept, by using u.v.-light as mutagenic agent generated strains with EPA and DHA contents about 32.8 and 32.9% (in % dry biomass) higher than those of the control, native strain (Meireles et al 2003). Use of process engineering, an on-line based controlled process in a model system has been employed to increase the production rates of both EPA and DHA by P. lutheri under various conditions of light and growth rate (Meireles et al 2008).…”
Section: Introductionmentioning
confidence: 94%
“…Often high doses of mutagen are applied to kill most microorganisms in order to increase frequency of generated mutants (Demain and Adrio 2008;Meireles et al 2002;Smith and Wood 1991). However, the optimum dose of mutagen is that which gives the highest proportion of desirable mutants in the surviving population.…”
Section: Introductionmentioning
confidence: 99%
“…However, some common characteristics of the strains, such as degeneration, weak adaptability, and low production, still hinder the large-scale production [6]. As a kind of simple and effective breeding strategy, mutagenesis is widely used for selecting various kinds of high-producing strains, Meireles [4] increased the yields of EPA and DHA by the microalga following mutagenesis, and it had also been shown to improve the EPA content of microalgae Phaeodactylum tricornutum via ultraviolet (UV) mutant [7].…”
mentioning
confidence: 99%
“…isolated from the ocean has attracted increasing attention. Although the industrial production of DHA has been achieved at very large scale, some methods were for attempts to improve DHA synthesis via intrinsic parameters [4] or extrinsic parameters [5]. However, some common characteristics of the strains, such as degeneration, weak adaptability, and low production, still hinder the large-scale production [6].…”
mentioning
confidence: 99%